Does local planning of fast-growing medium-sized towns lead to higher urban intensity or to sprawl? Cases from Zhejiang Province. (November 2022) - Guan, ChengHe; Wang, Yuanzhao; Keith, Michael; Li, Ying; Cao, Guangzhong
Abstract: Previous studies have frequently taken urban density as a surrogate for economic efficiency and applied composite scores such as urban intensity to assess the existing physical forms of towns. However, measures of intensity might nuance crude calculations of density while considering how such measures relate to future plans and the process of transformations. This paper used open source geospatial data and regulatory detailed planning to measure urban intensity of the existing and the planned. Spatial analytical techniques were applied to compute accessibility to destinations, building density, compactness of development, and diversity of land use function of sixteen specialty towns in China. The results showed that the regulatory detailed planning of these cases might not improve town planning measured by intensity in terms of spatial arrangement in the time horizon of 15–20 years. We found that well-integrated monocentric forms with the finer street network could potentially provide a more suitable spatial distribution for mid-sized towns measured by urban intensity, no matter whether the urban form is linear or center-spreading. Moreover, the comparison between the existing and the planned implies that the poly-centric urban form for mid-sized towns in China could end up with a lower score of urban intensity. We outline a framework of urban intensity measures that include analytical consideration of what is there now, planned to what is forthcoming, and conceptual in terms of time and space. Highlights: Differentiating urban intensity from density Using urban block as the spatial unit of study is more accurate than a synthetic spatial grid. Comparing existing and planned conditions of medium-sized towns Evaluation and intervention of town planning policies